Development of STEM-Integrated Static Fluid E-Modules to Improve Students' Creative Thinking and Science Process Skills - ilhamdi Siddiq; Asrizal Asrizal (JURNAL EKSAKTA PENDIDIKAN (JEP), 2023)
The 21st century learninghould apply the skills of grade 21 students which include the 4C skills, namely creative thinking, critical thinking, communication, and collaboration. This skill is needed in solving a problem. The learning outcomes show the low ability of students to think creatively and scientifically. The STEM integrated e-module is the solution to this problem. The purpose of this study was to determine the initial studies, the validity and practicality of using STEM integrated e-modules. This research method uses research and development research using the Hannafin and Peck development model. Research instruments include needs analysis instruments, validation questionnaires and practicality. The data analysis technique used is descriptive statistics. Based on the data that has been analyzed there are three research results. First, the results of the needs analysis obtained an average value of 69.4 in the good category. Second, product validation results obtained an average value of 84.1 with a very good category. Third, the product practicality results obtained an average value of 93 in the very good category. The implication of the results of this study is that teachers must construct students' skills through e-modules. The meaning of the results of this study is that the STEM integrated e-module is valid and practical for use in learning.